Low inter-diffusivity γ'-base bondcoats for single crystal superalloy René N5. Ⅱ: Cyclic oxidation behavior at 1100 ºC. (October 2019) - Yao, Hongrui; Yang, Lanlan; Bao, Zebin; Zhu, Shenglong; Wang, Fuhui
Highlights: The growth rates of TGO during cyclic oxidation were almost same as those during isothermal oxidation. Minor TGO spallation occurred on the Al-19 and Al-20 coatings, probably because of formation of Ta2 O5 particles within TGO. Severe TGO spallation occurred on the Al-25 coating, probably because of void formation at the TGO/coating interface. The γ'-base coatings has much high resistance against coating/substrate interdiffusion and coating rumpling. Abstract: Three γ'-base coatings of Hf-doped and Re-modified NiCoCrAlTaY system were deposited on René N5 superalloy by magnetron sputtering. The cyclic oxidation behavior of these coatings was investigated at 1100 °C for 500 h. The γ'-base coatings exhibited excellent resistance against coating/substrate interdiffusion and coating rumpling. The TGO was mainly alumina. Minor TGO spallation occurred on coatings with ˜19 at.% and 20 at.% Al, which may be correlated with the formation of Ta-rich oxide particles within TGO scales, while severe TGO spallation occurred on coating with ˜25 at.% Al, which may be correlated with the formation of voids at TGO/coating interface.